Biology of adeno-associated viral vectors in the central nervous system - Murlidharan, Giridhar; Samulski, Richard J.; Asokan, Aravind (Frontiers in Molecular Neuroscience, 2014)
Gene therapy is a promising approach for treating a spectrum of neurological and neurodegenerative disorders by delivering corrective genes to the central nervous system (CNS). In particular, Adeno-Associated Viruses (AAV) have emerged as promising tools for clinical gene transfer in a broad range of genetic disorders with neurological manifestations. In the current review, we have attempted to bridge our understanding of the biology of different AAV strains with their transduction profiles, cellular tropisms and transport mechanisms within the CNS. Continued efforts to dissect AAV-host interactions within the brain are likely to aid in the development of improved vectors for CNS-directed gene transfer applications in the clinic.